Strength Training with Superimposed Whole Body Vibration Does Not Preferentially Modulate Cortical Plasticity - Ashleigh T. Weier; Dawson J. Kidgell (The Scientific World Journal)
Paired-pulse transcranial magnetic stimulation (TMS) was used to investigate 4 wks of leg strength training with and without whole body vibration (WBV) on corticospinal excitability and short-latency intracortical inhibition (SICI). Participants (𝑛=12) were randomly allocated to either a control or experimental (WBV) group. All participants completed 12 squat training sessions either with (WBV group) or without (control group) exposure to WBV (𝑓=35 Hz, 𝐴=2.5 mm). There were significant (𝑃<0.05) increases in squat strength and corticospinal excitability and significant (𝑃<0.05) reductions in SICI for both groups following the 4 wk intervention. There were no differences detected between groups for any dependant variable (𝑃>0.05). It appears that WBV training does not augment the increase in strength or corticospinal excitability induced by strength training alone.